1960
DOI: 10.1111/j.1748-1716.1960.tb01953.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Position on the Circulation at Rest and During Exercise, with Special Reference to the Influence on the Stroke Volume

Abstract: B E V E G~, S., A. HOLMGREN and B. JONSSON. The eJect of body position on the circulation at rest and during exercise, with special reference to the inzuence on the stroke volume. Acta physiol. scand. 1960. 49. 279-298.-In 10 healthy, adult, male subjects the hemodynamics have been studied by the aid of heart catheterization at rest and during work both in supine and sitting positions. The cardiac output was on the average 2.2 l/min less in the sitting than in the supine position, both at rest and during exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
132
4
1

Year Published

1967
1967
1987
1987

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 429 publications
(159 citation statements)
references
References 18 publications
22
132
4
1
Order By: Relevance
“…Cardiac output is 1-2 liters/min higher in the supine than in the sitting position at rest and during dynamic exercise involving large muscle groups, e.g., bicycle exercise (21)(22)(23)(24)85,328,329). Body position does not affect the slope of the normal linear relationship between oxygen uptake and cardiac output.…”
Section: Postural Effects On Hemodynamic Responses To Exercisementioning
confidence: 81%
See 1 more Smart Citation
“…Cardiac output is 1-2 liters/min higher in the supine than in the sitting position at rest and during dynamic exercise involving large muscle groups, e.g., bicycle exercise (21)(22)(23)(24)85,328,329). Body position does not affect the slope of the normal linear relationship between oxygen uptake and cardiac output.…”
Section: Postural Effects On Hemodynamic Responses To Exercisementioning
confidence: 81%
“…The systemic arteriovenous oxygen difference also increases. A change from the supine to standing position causes qualitatively similar but slightly larger hemodynamic adjustments than a change from the supine to sitting position (23,24). Matalon and Farhi (224) demonstrated an inverse linear relationship between cardiac output and the sine of the tilting angle during passive head-up tilt.…”
Section: Cardiac Outputmentioning
confidence: 99%
“…In studies comparing full upright sitting and supine bicycle ergometry (without torso stabilization), peak workloads have been reported to be significantly greater in the full upright position (36), in the supine position (6), or not significantly different (1,14). In addition to undergoing multigated radionuclide angiography in both 70" tilt and supine positions, all 21 of our subjects also underwent full upright (90") bicycle ergometry with respiratory gas analysis to establish the level of maximal exercise capacity (plateau O2 consumption).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of blood and the hydrostatic forces acting between the cardiac pump and the peripheral vasculature are altered when a subject assumes different positions. Position-related differences in the hernodynamic and cardiac functional responses to exercise have been noted in normal subjects (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)37) and in patients with various types of heart disease (4,7, 12, 16-19); the specific results have, however, varied somewhat from study to study.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodynamic studies have generally, but not unanimously, shown that stroke volume increases with transition from rest to exercise in both the upright and supine positions. ", 4,[8][9][10][40][41][42] LV end-diastolic volume during supine exercise has been shown to decrease in studies in which metallic epicardial markers" and angiography were used.14 Using angiography, Gorlin et al12 found no substantial change in LV enddiastolic volume. Crawford et al6 demonstrated echocardiographically that diastolic diameter does not change during moderate supine and upright bicycle exercise.…”
Section: The Effects Of Exercisementioning
confidence: 99%